Evolution of Integrated Development in Urban Agglomerations in China - Guoqin Ge; Minhui Huang; Yazhou Zhou (Environmental Science and Sustainable Development)
Understanding the evolution of urban agglomerations is crucial for formulating resilient and inclusive spatial development policies. This study takes the Chengdu-Chongqing urban agglomeration in China as a case study, utilizing a modified gravity model to describe economic interactions among spatial units, measuring urban-rural equilibrium through income disparity, and applying Exploratory Spatial Data Analysis (ESDA) to examine the spatial associations between economic agglomeration and urban-rural balance. The main findings are as follows: (1) The intensity of economic linkages and the level of urban-rural equilibrium in the Chengdu-Chongqing urban agglomeration have significantly improved across the study area. (2) The spatial organization of the region shows a significant flattening trend, forming a significant “point-axis system” around the two core cities of Chengdu and Chongqing. (3) Regional imbalance continued to expand, exhibiting a distinct spatiotemporal co-evolution characterized by a “core-periphery” structure. The study concludes that the excessive dominance of core cities and the limited driving ability of sub-core cities are the main obstacles to the integrated development of the Chengdu-Chongqing urban agglomeration, and this study proposes development strategies from the aspects of improving infrastructure, promoting industrial transfer, and emphasizing institutional guidance.